Repercusiones psicológicas de la violencia intrafamiliar en las habilidades parentales en países latinoamericanos: revisión sistemática (2023)
The general objective of this study is to describe the psychological impact of domestic violence on parental skills in Latin American countries over the last ten years. To do this, a qualitative methodology with descriptive design was implemented, in which the systematization and analysis of scientific articles extracted and selected from virtual platforms and metasearch engines that have legitimacy and academic relevance was carried out